Human Trafficking in the Global South: A Bibliometric Analysis of Publications Using Scopus Database 2013-2024 - Muhammad Zahrul Anam, (Technium Social Sciences Journal, 2025)
Human trafficking is a wide-ranging crime with numerous victims and various patterns. The population living mainly in low and middle-income countries of the Global South is more vulnerable to being trafficked. Selected countries from the Middle East, Central Asia, Southeast Asia, South Asia, Africa, and Latin America are samples used to examine human trafficking of scholarly works between 2013 and 2023. This article investigates research trends on human trafficking in the Global South from Asia, Africa, the Middle East, and Latin America between 2012 and 2024. A bibliometric method was adopted. Articles published in the Scopus-indexed journals were retrieved. The research period was designated from 2013 to 2023. The articles that were retrieved closely related to the topic were three hundred thirty-five. The overall number of authors is seven hundred and twenty-one people. The average number of authors per document is 2.2. International co-authors are 29%. Then, there are typically 101 single authors, and each writer publishes roughly three articles. Migration is an issue that articles discuss the most (n=335;81 works), followed by sex trafficking (n=335;75 publications), slavery (n=335;70 articles), forced labor (n=335;34 articles), smuggling (n=335;34 publications), child trafficking (n=335;17), human experiment (n=335;6) and terrorism (n=335;1 works). Africa has more articles than other regions in the Global South. The top three active institutions are the University of Georgia (USA) (12 articles), the University of Sultan Ageng Tirtayasa (10 publications), and the University of Nigeria (9 publications). The Journal of Human Trafficking is a journal with the highest citation. The issue mainly cited in the Marine Policy journal is forced labor. Migration, sex trafficking, and slavery are the dominant issues several journals address in dealing with human trafficking in the Global South. The literature on the terrorism of human trafficking in the Global South was notably lacking. The human experiment also has little attention.